The Reality of Planning Efficiencies Among Department Heads at the University of Damascus (Journal of Hama University, 2020)
The aim of this research is to determine the reality of the planning efficiencies owned by the heads of departments at the University of Damascus (knowledge efficienciey - the efficienciey of setting the educational plan -  the efficienciey of implementation  the educational plan  -  the efficienciey of evaluating the educational plan and its follow-up) from the viewpoint of the department heads, and clarifying the differences between them according to the research variables (gender - years Experience - faculty Specialization), To achieve this, the researcher adopted the descriptive analytical method using a questionnaire that included 39 items distributed on the research axes(knowledge efficienciey - the efficiencies of setting the educational plan -  the efficiencie of implementation  the educational plan -  the efficienciey of evaluating the educational plan and its follow-up) and applied the questionnaire to a sample of 65 heads of department at Damascus University within the faculties , which were divided based on the specialization of the faculty ,the theory faculties are : education college, faculty of law, faculty of economics, faculty of media and practical faculty: The Faculty of Science, the Faculty of Human Medicine, Dentistry and the Faculty of Pharmacy, recovered (63) questionnaires, and excluded one questionnaire for incompleteness, to reach the final number of research sample members (62) individuals, and The research reached the following results:*The overall result came to the degree of department heads ’assessment at the University of Damascus for the reality of their planning efficiencies related to the four fields with an arithmetic average (2.10) and a relative weight (70.42), with an average degree of appreciation *There are no statistically significant differences at the level of significance (0.05) between the average estimates of department heads in Damascus University for the reality of their planning efficiencies according to the gender variable and the college's specialization (process, theory). *There are statistically significant differences at the level of significance (0.05) between the average estimates of department heads at Damascus University for the reality of planning efficiencies they have according to the variable of years of experience in favor of department heads who have more than 6 years experience